The Moderating Effect of Women Managers in the Internationalisation and Intellectual Capital-Performance Relationship - Andreu, Rosario; Rienda, Laura; Ruiz-Fernandez, Lorena (Transformations In Business & Economics, 2024)
Many studies have analysed the relationship between internationalisation and corporate profitability. However, certain variables that have been less studied may affect this relationship, such as the development of Intellectual Capital (IC) and the presence of women managers. From the knowledge-based perspective, IC is considered a mediating variable between internationalisation and profitability in this paper. Thus, both the direct and indirect effects of internationalisation on business performance are analysed. In addition, the presence of women in managerial positions is included as a possible moderating variable of the internationalisation-performance relationship. A more significant presence of women in management teams seems to be associated with a greater growth orientation and higher corporate profitability. The results obtained by applying PLS-SEM to a sample of 107 Spanish hotel chains confirm that IC mediates the internationalisation-performance relationship. In addition, the presence of female managers moderates the positive relationship between internationalisation and business profitability.